1994
DOI: 10.1172/jci117478
|View full text |Cite
|
Sign up to set email alerts
|

Diesel exhaust particles induce local IgE production in vivo and alter the pattern of IgE messenger RNA isoforms.

Abstract: Diesel exhaust particles (DEP) have been implicated in the increased incidence of allergic airway disorders. We investigated the effects of DEP on localized immunoglobulin production by performing nasal challenges with varying doses of DEP and analyzing the local immune response in nasal lavages obtained before and after. A significant rise in nasal IgE but not IgG, IgA, IgM, or albumin was observed in subjects 4 d after challenge with 0.30 mg DEP, equivalent to exposure on an average Los Angeles day. Direct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
207
1
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 354 publications
(214 citation statements)
references
References 30 publications
4
207
1
2
Order By: Relevance
“…Diesel exhaust has been of concern for many decades due to its health effects and climate impact (Diaz-Sanchez et al, 1994). The emission standards for diesel engines have become more and more stringent since the 1980s.…”
Section: Introductionmentioning
confidence: 99%
“…Diesel exhaust has been of concern for many decades due to its health effects and climate impact (Diaz-Sanchez et al, 1994). The emission standards for diesel engines have become more and more stringent since the 1980s.…”
Section: Introductionmentioning
confidence: 99%
“…In experimental chamber studies, DE has been shown to cause airway symptoms [13] and to induce an acute inflammatory response in human airways as reflected in bronchoalveolar lavage [14,15] and bronchial biopsy [16] samples. Further, local nasal challenge with DE particles has been reported to enhance immunoglobulin E production in the nose [17] and to cause an increased cytokine response in the nose of allergic subjects [18].…”
mentioning
confidence: 99%
“…Early studies by Matsumura (1970) and Osebold et al (1980) showed that ozone exposure enhanced allergic type immune responses in guinea pigs and mice. Later experiments in mice showed that inhalation of fresh DE or intrapulmonary instillation of DE particles (DEP) caused adjuvant activity resulting in increased sensitization to experimental allergens (Muranaka et al, 1986;Takano et al, 1998;Takahashi et al, 2010), although similar effects were also shown in humans (Diaz-Sanchez et al, 1994;Zhang et al, 2009). In terms of exposures during pregnancy, it is well-established that in utero exposure to cigarette smoke can have profound effects on reproductive health, childhood obesity, type 2 diabetes, allergic airway symptoms, and cancer (Doherty et al, 2009;Tsai et al, 2010).…”
Section: Research Articlementioning
confidence: 99%